Applying Supply Chain Management in a Web-Based Drug Inventory System - Maysaroh Maysaroh; Muhammad Ardiansyah Sembiring; Sudarmin Sudarmin (Pusat Teknologi Informasi dan Pangkalan Data IAIN Syekh Nurjati Cirebon, 2025)
The advancement of information technology has driven digitalization across various sectors, including drug inventory management in the pharmaceutical field. Toko Obat Lamtama still faces challenges in stock management due to the absence of a computerized system, leading to risks of stock shortages, surpluses, and expired medications. This study aims to design and implement a web-based drug inventory information system integrated with the concept of Supply Chain Management (SCM) to improve operational efficiency and customer service. The methodology includes needs analysis, system design using UML, and implementation of a web-based system. The results show that the system can automate the processes of recording, monitoring, and ordering drugs more accurately, while also supporting faster and more precise decision-making. The implementation of SCM within this information system has also successfully reduced waste caused by unused medications and enhanced the efficiency of supply chain management.